Leadership for sustainable development in the context of higher education institutions - Eustachio, João Henrique Paulino Pires (2022)
Companies are expected to reduce negative externalities and promote positive impacts in order to contribute to the 2030 Agenda for Sustainable Development. However, this is not a simple task; it requires corporate social responsibility (CSR) engagement through effective coordinated actions to successfully implement the sustainable development goals (SDGs) into the companies\' managerial systems and strategies. Among the several theoretical streams, change management calls attention since it shows how companies can deal with the transition towards becoming more sustainability-oriented, where leadership is not only desired but essential in this process. This complex process is also evidenced in the context of higher education institutions (HEIs), where sustainability leadership (SL) can be related to (1) the role of administrative staff in implementing the SDGs into the universities´ educational systems, (2) the support offered to professors so they can implement sustainability in teaching practices and (3) the role the professor as a sustainability leader, capable of educating the students who are also expected to become sustainability leaders in the future by the time they assume important positions in companies. In this sense, considering the relevance of SL to both companies and HEIs, this thesis aims to explore the theoretical foundations of the concept of SL and its implications in the context of HEIs by presenting three studies. The first study aims to unveil the landscape of SL literature based on well-cited papers published in top journals. A total of 1813 articles were explored through the bibliometric assessment. The second aims to understand the influence of SL and transformational leadership in the HEIs´ social innovation tendency and implementation of sustainability aspects in teaching practices through a world survey with 603 professors from 102 countries. The third study tackles the context of business schools, aiming to understand the extent to which there are differences between professors from PRME signatory and non-signatory business schools in terms of adopting SD aspects in their teaching and the support they receive from their HEIs in this process. The results indicate that SL is a complex and broad concept, which can also be used in the HEIs and companies´ context as responsibility leadership, and corporate SL. The results from the structural equation modelling evidence that SL has a significantly strong relationship with transformational leadership, social innovation tendency and adoption of sustainability aspects in teaching; however, it is not possible to support the existence of a significant relationship between transformational leadership and adoption of sustainability aspects in teaching, and between social innovation tendency and adoption of sustainability aspects in teaching. Finally, the last study evidenced the importance of the context influencing the relationship of the stakeholders in HEIs, where hypotheses testing showed that professors from PRME business schools significantly tend to implement sustainability aspects into teaching and receive more support from their superiors and institutions when compared to those who belong to non-signatory schools. Theoretical and practical implications, as well as opportunities for future studies are also addressed.